Computerised Brain Tumours Classification using MRI Images - Namachivayam, A.; Puviarasan, N. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The categories of the brain tumours into four categories no tumour, glioma, meningioma, and pituitary are exploited in this study to propose a unique representation for magnetic resonance image analysis. MRI images are the input in this investigation. Radiologists manually interpret MRI scans to find abnormalities in the brain. Interpreting a large number of images by hand is difficult and time-consuming. However, because of the complexity of the MRI equipment, this undertaking is not easy. Particularly, it can be difficult and very subjective to differentiate between various tumour forms, such as gliomas, meningiomas, and pituitary tumours. Computer-based detection aids in the precise, quick, and accurate identification of the disease to address this issue. The suggested study employs CNN and SVM models. Using HOG characteristics, the SVM classifier categorises the brain MRI picture. Three convolutional layers were used in the CNN model's training, and the softmax classifier is used to categorise the image. The four forms of brain tumours identified by the SVM and CNN models are no tumour, glioma, meningioma, and pituitary. By comparing the outcomes, CNN estimates accuracy to be 97%, whereas SVM estimates accuracy to be 92%.